Lithium manganese iron phosphate composite material as well as preparation method and application thereof

Through boron doping and coating technology, the structural stability and electrochemical performance of lithium manganese iron phosphate composite materials are improved, and the problem of poor structural stability is solved, and better cycling performance and rate performance are achieved.

CN119905568AActive Publication Date: 2025-04-29HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510139320.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-04-29
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

The structural stability of lithium manganese iron phosphate composite materials is poor, resulting in poor rate performance and cycle life.

Method used

Through boron doping and coating technology, boron-doped lithium manganese iron phosphate and its boron-containing coating materials are prepared. Boron atoms form doping in transition metal oxide crystals to improve structural stability, and the electrolyte is separated by the coating material to reduce side reactions and manganese dissolution.

Benefits of technology

The structural stability, circulation performance and rate performance of lithium manganese iron phosphate composite materials have been significantly improved, and the cycle life of the battery has been extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005264282070000061
    Figure BDA0005264282070000061
  • Figure BDA0005264282070000071
    Figure BDA0005264282070000071
  • Figure BDA0005264282070000072
    Figure BDA0005264282070000072
Patent Text Reader

Abstract

The invention discloses a lithium manganese iron phosphate composite material as well as a preparation method and application thereof, and belongs to the technical field of lithium batteries. The lithium manganese iron phosphate composite material comprises a boron-doped lithium manganese iron phosphate material and a boron-containing coating material coating the surface of the boron-doped lithium manganese iron phosphate material, the invention also provides a preparation method of the lithium iron manganese phosphate composite material. The preparation method comprises the following steps: S1, preparing a mixed solution A containing iron, manganese, phosphorus and boron elements; s2, adjusting the pH value of the mixed solution A; s3, drying the mixed solution A to obtain a dried product B; and S4, mixing the dried product B with a lithium element, and calcining to obtain the lithium manganese iron phosphate composite material. The main purpose of the invention is to provide the lithium manganese iron phosphate composite material with good structural stability. And moreover, a simple sol-heat treatment process can be adopted, and a one-step sintering preparation method is simple in process flow and suitable for industrial mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and more specifically, to a lithium manganese iron phosphate composite material and a preparation method and application thereof. Background Art

[0002] At present, the main cathode materials for commercial lithium-ion batteries are lithium cobalt oxide, lithium manganese oxide and lithium iron phosphate. Compared with lithium cobalt oxide with layered structure and lithium manganese oxide with spinel structure, lithium iron phosphate material with olivine structure has the advantages of stable working voltage, high theoretical capacity, stable structure and high temperature performance. However, lithium iron phosphate has a lower voltage platform (3.4V) and its energy density is lower. Lithium manganese iron phosphate has the same structure as lithium iron phosphate. While maintaining the advantages of lithium iron phosphate, it also has a higher discharge platform (4.1V) and higher energy density. Therefore, the development of lithium manganese iron phosphate with excellent electrochemical performance as a cathode material for lithium-ion batteries has a very broad market prospect.

[0003] However, the conductivity and ion diffusion coefficient of lithium manganese iron phosphate materials are 1-2 orders of magnitude smaller than those of lithium iron phosphate, and the rate performance of lithium manganese iron phosphate materials is poor. In addition, after the manganese and iron in the lithium manganese iron phosphate material are mutually dissolved, the crystal structure of the material will be distorted during the charge and discharge process, and manganese may be dissolved during the battery cycle and react with the electrolyte, thereby affecting the battery cycle life. The prior art reports some methods of improving the electrochemical properties of lithium manganese iron phosphate materials or obtained lithium manganese iron phosphate composite materials by doping, coating, etc., such as by doping with metal elements, carbon coating, etc., but there is still a problem of poor electrochemical performance.

[0004] Therefore, there is an urgent need for a lithium manganese iron phosphate composite material with excellent chemical properties such as rate performance and structural stability. Summary of the invention

[0005] 1. Technical problem to be solved by the invention

[0006] Aiming at the problem of poor structural stability of lithium iron manganese phosphate composite materials in the prior art, a lithium iron manganese phosphate composite material is provided.

[0007] 2. Technical solution

[0008] In order to achieve the above object, the technical solution provided by the present invention is:

[0009] A lithium manganese iron phosphate composite material of the present invention,

[0010] The lithium manganese iron phosphate composite material comprises a boron-doped lithium manganese iron phosphate material and a boron-containing coating material coated on the surface of the boron-doped lithium manganese iron phosphate material.

[0011] It should be noted that in the boron-doped lithium manganese iron phosphate material and the boron-containing coating material, the boron atoms occupy the octahedral interstitial positions in the transition metal oxide crystals to form doping and bond with the lattice oxygen, thereby improving the structural stability of the lithium manganese iron phosphate composite material and improving its cycle performance;

[0012] On the other hand, the boron-containing coating material can separate the boron-doped lithium manganese iron phosphate material from the electrolyte, reduce the side reactions with the electrolyte, effectively inhibit the dissolution of manganese, and improve the stability of the lithium manganese iron phosphate composite material.

[0013] Preferably, the coating material forms a layer on the surface of the boron-doped lithium manganese iron phosphate material as much as possible.

[0014] Preferably, the coating material forms a coating layer on the surface of the boron-doped lithium manganese iron phosphate material.

[0015] It should be noted that the coating material forms a coating layer on the surface of the boron-doped lithium manganese iron phosphate material, which is more conducive to separating the boron-doped lithium manganese iron phosphate material from the electrolyte, reducing side reactions with the electrolyte, and can effectively inhibit manganese dissolution and improve the stability of the lithium manganese iron phosphate composite material.

[0016] Furthermore, the chemical formula of the boron-doped lithium manganese iron phosphate material is LiFe 1-x-y Mn x B y PO4, where 0.01<x<0.9, 0.01<y≤0.1;

[0017] The chemical formula of the boron-containing coating material is LiMn 2-z B z O4, where 0.01<z≤0.1.

[0018] It should be noted that the specific chemical formula of the boron-doped lithium manganese iron phosphate material is as described above, and the boron atoms occupy the octahedral interstitial positions in the transition metal oxide crystals to form doping and bond with the lattice oxygen, thereby improving the structural stability of the lithium manganese iron phosphate composite material; the boron-containing coating material LiMn 2-z B z O4 is electrochemically active and can enhance the migration of lithium ions or electrons, thereby improving the rate performance of lithium manganese iron phosphate composite materials.

[0019] Preferably, the chemical formula of the boron-doped lithium manganese iron phosphate material is LiFe 1-x-y Mn x B y PO4, where 0.01<x<0.9, 0.01<y<0.1;

[0020] The chemical formula of the boron-containing coating material is LiMn 2-z Bz O4, wherein 0.01<z<0.1.

[0021] Furthermore, the molar amount of the boron-containing coating material accounts for a molar amount of the lithium manganese iron phosphate composite material of m, and 0.5%≤m≤5%.

[0022] It should be noted that, when the molar amount of the boron-containing coating material to the molar amount of the lithium iron manganese phosphate composite material is controlled within the above range, the lithium iron manganese phosphate composite material can have better cycle performance.

[0023] Furthermore, the particle size of the lithium manganese iron phosphate composite material is D50≤15 μm.

[0024] For example, it may be 15 μm, 12 μm, 9 μm, 6 μm, 3 μm or 1 μm.

[0025] It should be noted that the lithium manganese iron phosphate composite material has a more suitable particle size, which is conducive to further improving the comprehensive performance of the material.

[0026] Furthermore, the thickness of the boron-containing coating material is 0.1 to 3 mm.

[0027] The present invention also provides a method for preparing a lithium iron manganese phosphate composite material, comprising the following steps:

[0028] S1. Preparing a mixed solution A containing iron, manganese, phosphorus and boron elements;

[0029] S2. adjusting the pH value of the mixed solution A;

[0030] S3. Drying the mixed solution A to obtain a dry product B;

[0031] S4. The dried product B is mixed with lithium element and then calcined to obtain a lithium iron manganese phosphate composite material.

[0032] It should be noted that the preparation method using a simple sol-heat treatment process and one-step sintering has a simple process flow and is suitable for industrial mass production.

[0033] Furthermore, in step S4, the calcination includes a primary calcination and a secondary calcination performed sequentially.

[0034] The primary calcination temperature is 400-600°C, the time is 3-8h, and the heating rate is 3°C / min-10°C / min;

[0035] The secondary calcination is carried out at a temperature of 600 to 900° C., for a time of 8 to 20 hours, and at a heating rate of 3° C. / min to 10° C. / min.

[0036] It should be noted that during high-temperature calcination, due to the small ionic radius of boron atoms, they are easily diffused into the crystal phase of the boron-doped lithium manganese iron phosphate material and the boron-containing coating material, so that the boron atoms are evenly distributed in the boron-doped lithium manganese iron phosphate material and the boron-containing coating material, and occupy the octahedral interstitial positions in the transition metal oxide crystals in the boron-doped lithium manganese iron phosphate material and the boron-containing coating material to form doping and bond with lattice oxygen, thereby improving the structural stability of the lithium manganese iron phosphate composite material;

[0037] Through primary calcination and secondary calcination, and controlling the temperature, time and heating rate of the primary calcination and the secondary calcination within the above-mentioned range, boron atoms can be diffused into the crystal phases of the boron-doped lithium manganese iron phosphate material and the boron-containing coating material, so as to enhance the structural stability of the lithium manganese iron phosphate composite material and have excellent rate and cycle performance.

[0038] For example, the primary calcination temperature may be 400°C, 500°C or 600°C, the time may be 3h, 5h, 7h or 8h, and the heating rate may be 3°C / min, 5°C / min, 7°C / min or 10°C / min;

[0039] The temperature of the secondary calcination can be 600°C, 700°C, 800°C or 900°C, the time can be 8h, 10h, 12h, 14h, 16h, 18h or 20h, and the heating rate can be 3°C / min, 5°C / min, 7°C / min or 10°C / min.

[0040] Furthermore, the molar ratio of lithium, iron, manganese, phosphorus and boron elements is (1 to 1.5): [(1-m) × (1-xy)]: [(1-m) × x + m × (2-z)]: 1: [m × z + (1-m) × y], wherein 0.01 < x < 0.9, 0.01 < y ≤ 0.1, 0.01 < z ≤ 0.1, 0.5 ≤ m ≤ 5%.

[0041] It should be noted that the molar ratio of the lithium, iron, manganese, phosphorus and boron elements is within the above range, so that the prepared boron-doped lithium manganese iron phosphate material and the boron-containing coating material have the above chemical formula, so as to obtain a lithium manganese iron phosphate composite material with good stability and good rate performance;

[0042] In addition, by adjusting the molar ratio of lithium, iron, manganese, phosphorus and boron elements, the molar proportion of the boron-containing coating material in the lithium manganese iron phosphate composite material can be controlled to adjust the performance of the lithium manganese iron phosphate composite material.

[0043] Further, in step S3, the chemical formula of the dried product B is Mn 2-z B z (OH)2@Fe 1-x-y Mn x By PO4, wherein 0.01<x<0.9, 0.01<y≤0.1, 0.01<z≤0.1.

[0044] Furthermore, in step S4, the lithium element comes from one, two or more of lithium carbonate, lithium hydroxide and lithium oxalate.

[0045] Furthermore, in step S1, the iron element comes from one, two or more of iron oxide, iron hydroxide, iron sulfate and iron oxalate.

[0046] Furthermore, in step S1, the manganese element comes from one, two or more of manganese carbonate, manganous sulfate and manganese oxide.

[0047] Furthermore, in step S1, the phosphorus element comes from one, two or more of phosphoric acid, lithium dihydrogen phosphate and lithium hydrogen phosphate.

[0048] Furthermore, in step S1, the boron element comes from one or both of boric acid and boron oxide.

[0049] Furthermore, step S1 may specifically include: dispersing the iron source, manganese source, phosphorus source and boron source into a solvent, stirring evenly, and obtaining a mixed solution A.

[0050] Further, the stirring speed is 500-700 rpm;

[0051] The stirring may be performed under heating conditions of 40 to 50°C.

[0052] Furthermore, the solvent of the mixed solution A is one or more of water and alcohol-based solvents.

[0053] Furthermore, the alcohol-based solvent is ethanol.

[0054] Furthermore, in step S2, an acid solution is used to adjust the pH value of the mixed solution A to 0-6.0.

[0055] It should be noted that adjusting the pH value of the mixed solution A to 0 to 6.0 can prevent the generation of metal hydroxide precipitation in the mixed solution A.

[0056] Furthermore, the acid solution is one, two or more of citric acid, sulfuric acid, hydrochloric acid and nitric acid.

[0057] Furthermore, in step S3, the drying temperature is 110-200° C. and the drying time is 24-48 hours.

[0058] It should be noted that the mixed solution A can be dried to remove excess solvent, and the raw material after drying has better stability, which is beneficial to improving the effect of high-temperature calcination to obtain a lithium manganese iron phosphate composite material with excellent performance.

[0059] In step S4, the mixing method is dry grinding, and the grinding time is 30 to 60 minutes.

[0060] For example, an agate mortar may be used for grinding.

[0061] Furthermore, the primary calcination and the secondary calcination are both carried out under a protective atmosphere.

[0062] It should be noted that the protective atmosphere can protect the deposited product from being affected by oxidation or other chemical reactions during the primary calcination and the secondary calcination.

[0063] Furthermore, the protective atmosphere may be an inert gas atmosphere.

[0064] For example, the inert gas atmosphere may be a nitrogen atmosphere.

[0065] The present invention also provides a lithium ion battery, which comprises a positive electrode and a negative electrode; the positive electrode comprises the above-mentioned lithium iron manganese phosphate composite material or the lithium iron manganese phosphate composite material prepared by the above-mentioned method.

[0066] It should be noted that the positive electrode of the lithium battery includes the lithium manganese iron phosphate composite material, so that the lithium battery has good electrochemical properties such as initial charge and discharge efficiency and cycle performance.

[0067] 3. Beneficial effects

[0068] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:

[0069] (1) The lithium iron manganese phosphate composite material provided by the present invention comprises a boron-doped lithium iron manganese phosphate material and a boron-containing coating material coated on the surface of the boron-doped lithium iron manganese phosphate material, wherein the boron atoms occupy the octahedral interstitial positions in the transition metal oxide crystals to form doping and bond with the lattice oxygen, thereby improving the structural stability of the lithium iron manganese phosphate composite material and improving its cycle performance and rate performance;

[0070] On the other hand, the boron-containing coating material can separate the boron-doped lithium manganese iron phosphate material from the electrolyte, reduce the side reactions with the electrolyte, effectively inhibit the dissolution of manganese, and improve the stability of the lithium manganese iron phosphate composite material.

[0071] (2) The lithium iron manganese phosphate composite material provided by the present invention, LiMn 2-z B zO4 is electrochemically active and can enhance the migration of lithium ions or electrons, thereby improving the rate performance of lithium manganese iron phosphate composite materials.

[0072] (3) The preparation method of the lithium iron manganese phosphate composite material provided by the present invention, during high-temperature calcination, due to the small ionic radius of boron atoms, it is easy to diffuse into the crystal phase of the boron-doped lithium iron manganese phosphate material and the boron-containing coating material, occupy the octahedral interstitial positions in the transition metal oxide crystals in the boron-doped lithium iron manganese phosphate material and the boron-containing coating material to form doping and bond with lattice oxygen, thereby improving the structural stability of the lithium iron manganese phosphate composite material.

[0073] (4) By adopting a simple sol-heat treatment process, the preparation method through one-step sintering has a simple process flow and is suitable for industrial mass production.

[0074] (5) The lithium battery provided by the present invention has a positive electrode comprising the lithium iron manganese phosphate composite material, so that the lithium battery has good electrochemical properties such as initial charge and discharge efficiency and cycle performance. DETAILED DESCRIPTION

[0075] The present disclosure may be more easily understood by reference to the following description in conjunction with examples, all of which constitute a part of the present disclosure. It should be understood that the present disclosure is not limited to the specific products, methods, conditions or parameters described and / or illustrated herein. Further, the terms used herein are only used for the purpose of describing specific embodiments by way of example and are not intended to be limiting unless otherwise indicated.

[0076] It should also be understood that, for the sake of clarity, certain features of the present disclosure may be described herein in the context of separate embodiments, but may also be provided in combination with each other in a single embodiment. That is, unless clearly incompatible or specifically not included, each separate embodiment is considered to be combinable with any other embodiment, and the combination is considered to represent another different embodiment. Conversely, for the sake of simplicity, the various features of the present disclosure described in the context of a single embodiment may also be provided individually or in any sub-combination. Finally, although a particular embodiment may be described as part of a series of steps or part of a more general structure, each step or substructure itself may also be considered to be an independent embodiment.

[0077] Unless otherwise indicated, it should be understood that each individual element in a list and each combination of individual elements in the list will be interpreted as a different embodiment. For example, a list of embodiments represented as "A, B, or C" should be interpreted to include embodiments "A", "B", "C", "A or B", "A or C", "B or C", or "A, B, or C".

[0078] When items are described by using the conjunction terms "... and / or...," etc., the description should be understood to include any one of the associated listed items and all combinations of one or more thereof.

[0079] In general, the use of the term "about" indicates an approximate value that can vary depending on the desired properties obtained by the disclosed subject matter, and will be interpreted in a context-dependent manner based on function. Therefore, one of ordinary skill in the art will be able to interpret a certain degree of difference on a case-by-case basis. In some cases, the number of significant figures used when expressing a particular value can be a representative technique for determining the difference allowed by the term "about". In other cases, a gradient in a range of values ​​can be used to determine the range of differences allowed by the term "about". Further, all ranges in this disclosure are inclusive and combinable, and reference to a value in a range includes each value within that range.

[0080] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs; the terms used herein and / or include any and all combinations of one or more of the associated listed items.

[0081] In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be purchased commercially.

[0082] The present invention is further described below in conjunction with specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. The essential characteristics and remarkable effects of the present invention can be reflected from the following examples, and the described embodiments are part of the embodiments of the present invention, rather than all the embodiments, and therefore, they do not limit the present invention in any way, and those skilled in the art make some non-essential improvements and adjustments based on the content of the present invention, which all belong to the protection scope of the present invention.

[0083] Example 1

[0084] Iron sulfate, manganese oxide, phosphoric acid and boric acid were placed in a 500mL beaker containing 300mL water at a molar ratio of 0.15:0.619:1:0.101, and the beaker was placed in a 45°C constant temperature water bath and stirred at 600rpm. After stirring evenly, the pH value was adjusted to 5 with sulfuric acid. The beaker containing the mixture was placed in a blast drying oven at 110°C for 30h. Lithium carbonate and the above-mentioned iron sulfate, manganese oxide, phosphoric acid and boric acid were ground in an agate mortar at a molar ratio of 0.52:0.15:0.619:1:0.101 and the dried product was placed in a porcelain boat, heated at a heating rate of 5°C / min in a tubular furnace, calcined at 450°C for 5h and 600°C for 12h in a nitrogen atmosphere to obtain a coating layer of LiMn 1.9 B 0.1 O4 molar percentage is 1% LiMn 1.9 B 0.1 O4@LiFe 0.3 Mn 0.6 B 0.1 PO4 lithium manganese iron phosphate composite material.

[0085] The prepared lithium manganese iron phosphate composite material, conductive carbon black, and PVDF (polyvinylidene fluoride) were added to NMP (N-methylpyrrolidone) in a mass ratio of 96%: 2%: 2%, mixed evenly, and coated and rolled to prepare a positive electrode sheet. In addition, graphite, conductive carbon black, SBR (styrene butadiene rubber), and CMC (carboxymethyl cellulose) were added to deionized water in a mass ratio of 95%: 2%: 2%: 1%, mixed evenly, and coated and rolled to prepare a negative electrode sheet. After assembling the positive and negative electrode sheets into a battery, the electrochemical performance of the battery was tested.

[0086] Table 1 First charge and discharge cycle conditions in Example 1

[0087]

[0088]

[0089] After testing, the battery has an initial charge and discharge efficiency of 90.5%, and a capacity retention rate of 90.5% after 600 cycles at 1C.

[0090] Example 2

[0091] Iron sulfate, manganese oxide, phosphoric acid and boric acid were placed in a 500mL beaker containing 300mL water at a molar ratio of 0.15:0.638:1:0.102, and the beaker was placed in a 45°C constant temperature water bath and stirred at 600rpm for uniform stirring; the pH value was adjusted to 5 with sulfuric acid; the beaker containing the mixture was then placed in a blast drying oven at 110°C for 30h. Lithium carbonate and the above-mentioned iron sulfate, manganese oxide, phosphoric acid and boric acid were ground with an agate mortar at a molar ratio of 0.550.15:0.638:1:0.102 and the dried product was placed in a porcelain boat, heated at a heating rate of 5°C / min in a tubular furnace, calcined at 450°C for 5h and 600°C for 12h in a nitrogen atmosphere to obtain a coating layer of LiMn 1.9 B 0.1 O4 molar percentage is 2% LiMn 1.9 B 0.1 O4@LiFe 0.3 Mn 0.6 B 0.1 PO4 lithium manganese iron phosphate composite material.

[0092] The lithium manganese iron phosphate, conductive carbon black, and PVDF prepared above were added to NMP in a mass ratio of 96%:2%:2%, mixed evenly, and then coated and rolled to prepare the positive electrode sheet. In addition, graphite, conductive carbon black, SBR, and CMC were added to deionized water in a mass ratio of 95%:2%:2%:1%, mixed evenly, and then coated and rolled to prepare the negative electrode sheet. After the positive and negative electrode sheets were assembled into a battery, the electrochemical performance of the battery was tested:

[0093] Table 2 First charge and discharge cycle conditions in Example 2

[0094]

[0095] After testing, the battery has an initial charge and discharge efficiency of 91.0%, and a capacity retention rate of 91.2% after 600 cycles at 1C.

[0096] Example 3

[0097] Iron sulfate, manganese oxide, phosphoric acid and boric acid were placed in a 500mL beaker containing 300mL water at a molar ratio of 0.15:0.657:1:0.103, and the beaker was placed in a 45°C constant temperature water bath and stirred at 600rpm for uniform mixing; the pH value was adjusted to 5 with sulfuric acid; the beaker containing the mixture was placed in a blast drying oven at 110°C for 30h. Lithium carbonate and the above-mentioned iron sulfate, manganese oxide, phosphoric acid and boric acid were ground in an agate mortar at a molar ratio of 0.58:0.15:0.657:1:0.103 and the dried product was placed in a porcelain boat, heated at a heating rate of 5°C / min in a tubular furnace, calcined at 450°C for 5h and 600°C for 12h in a nitrogen atmosphere to obtain a coating layer of LiMn 1.9 B 0.1 O4 molar percentage is 3% LiMn 1.9 B 0.1 O4@LiFe 0.3 Mn 0.6 B 0.1 PO4 lithium manganese iron phosphate composite material.

[0098] The prepared lithium manganese iron phosphate composite material, conductive carbon black, and PVDF were added to NMP in a mass ratio of 96%:2%:2%, mixed evenly, and coated and rolled to prepare a positive electrode sheet. In addition, graphite, conductive carbon black, SBR, and CMC were added to deionized water in a mass ratio of 95%:2%:2%:1%, mixed evenly, and coated and rolled to prepare a negative electrode sheet. After the positive and negative electrode sheets were assembled into a battery, the electrochemical performance of the battery was tested.

[0099] Table 3 First charge and discharge cycle conditions in Example 3

[0100]

[0101] After testing, the battery's initial charge and discharge efficiency was 92.3%, and after 600 cycles at 1C, the capacity retention rate was 92.5%.

[0102] Example 4

[0103] Iron sulfate, manganese oxide, phosphoric acid and boric acid were placed in a 500mL beaker containing 300mL water at a molar ratio of 0.15:0.676:1:0.104, and the beaker was placed in a 45°C constant temperature water bath and stirred at 600rpm for uniform stirring; the pH value was adjusted to 5 with sulfuric acid; the beaker containing the mixture was placed in a blast drying oven at 110°C for 30h. Lithium carbonate and the above-mentioned iron sulfate, manganese oxide, phosphoric acid and boric acid were ground in an agate mortar at a molar ratio of 0.6:0.15:0.676:1:0.104 and the dried product was placed in a porcelain boat, heated at a heating rate of 5°C / min in a tubular furnace, calcined at 450°C for 5h and 600°C for 12h in a nitrogen atmosphere to obtain a coating layer of LiMn 1.9 B 0.1 O4 molar percentage is 4% LiMn 1.9 B 0.1 O4@LiFe 0.3 Mn 0.6 B 0.1 PO4 lithium manganese iron phosphate composite material.

[0104] The prepared lithium manganese iron phosphate composite material, conductive carbon black, and PVDF were added to NMP in a mass ratio of 96%:2%:2%, mixed evenly, and coated and rolled to prepare a positive electrode sheet. In addition, graphite, conductive carbon black, SBR, and CMC were added to deionized water in a mass ratio of 95%:2%:2%:1%, mixed evenly, and coated and rolled to prepare a negative electrode sheet. After the positive and negative electrode sheets were assembled into a battery, the electrochemical performance of the battery was tested.

[0105] Table 4 First charge and discharge cycle conditions in Example 4

[0106]

[0107] After testing, the battery's initial charge and discharge efficiency was 90.1%, and after 600 cycles at 1C, the capacity retention rate was 90.3%.

[0108] Comparative Example 1

[0109] Iron sulfate, manganese oxide, and phosphoric acid were placed in a 500mL beaker containing 300mL of water at a molar ratio of 0.4:0.6:1, and the beaker was placed in a 45°C constant temperature water bath and stirred at 600rpm for uniform mixing; the pH value was then adjusted to 5; the beaker containing the mixture was placed in a blast drying oven at 110°C for 30h. Lithium carbonate was ground with the above-mentioned iron sulfate, manganese oxide, phosphoric acid, and boric acid at a molar ratio of 0.5:0.4:0.6:1 using an agate mortar for 60min and the dried product was placed in a porcelain boat, heated at a rate of 5°C / min in a tubular furnace, calcined at 450°C for 5h and 600°C for 12h in a nitrogen atmosphere to obtain LiFe 0.4Mn 0.6 PO4 lithium manganese iron phosphate composite material.

[0110] The prepared lithium manganese iron phosphate composite material, conductive carbon black, and PVDF were added to NMP in a mass ratio of 96%:2%:2%, mixed evenly, and coated and rolled to prepare a positive electrode sheet. In addition, graphite, conductive carbon black, SBR, and CMC were added to deionized water in a mass ratio of 95%:2%:2%:1%, mixed evenly, and coated and rolled to prepare a negative electrode sheet. After the positive and negative electrode sheets were assembled into a battery, the electrochemical performance of the battery was tested.

[0111] Table 5 First charge and discharge cycle conditions in comparative example 1

[0112]

[0113] After testing, the battery's initial charge and discharge efficiency was 89.0%, and the capacity retention rate was 88.6% after 600 cycles at 1C. This may be because the dissolution of Mn during the cycle destroyed the negative electrode SEI film, resulting in the loss of active lithium.

[0114] It can be seen from the data of the above examples and comparative examples that the lithium manganese iron phosphate composite material can effectively improve the electrochemical properties of the battery, such as the initial charge and discharge efficiency and cycle performance.

Claims

1. A lithium manganese iron phosphate composite material, characterized in that: The lithium manganese iron phosphate composite material comprises a boron-doped lithium manganese iron phosphate material and a boron-containing coating material coated on the surface of the boron-doped lithium manganese iron phosphate material.

2. The lithium iron manganese phosphate composite material according to claim 1, characterized in that: The chemical formula of the boron-doped lithium manganese iron phosphate material is LiFe 1-x-y Mn x B y PO4, where 0.01<x<0.9, 0.01<y≤0.1; The chemical formula of the boron-containing coating material is LiMn 2-z B z O4, where 0.01<z≤0.

1.

3. The lithium manganese iron phosphate composite material according to any one of claims 1 to 2, characterized in that: The molar amount of the boron-containing coating material accounts for a molar amount of the lithium manganese iron phosphate composite material of m, and 0.5%≤m≤5%.

4. A method for preparing the lithium manganese iron phosphate composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Preparing a mixed solution A containing iron, manganese, phosphorus and boron elements; S2. adjusting the pH value of the mixed solution A; S3. Drying the mixed solution A to obtain a dry product B; S4. The dried product B is mixed with lithium element and then calcined to obtain a lithium iron manganese phosphate composite material.

5. The method for preparing the lithium iron manganese phosphate composite material according to claim 4, characterized in that: In step S4, the calcination includes a primary calcination and a secondary calcination performed sequentially. The primary calcination temperature is 400-600°C, the time is 3-8h, and the heating rate is 3°C / min-10°C / min; The secondary calcination is carried out at a temperature of 600 to 900° C., for a time of 8 to 20 hours, and at a heating rate of 3° C. / min to 10° C. / min.

6. The method for preparing the lithium iron manganese phosphate composite material according to claim 5, characterized in that: The molar ratio of lithium, iron, manganese, phosphorus and boron elements in the lithium manganese iron phosphate composite material is (1-1.5): [(1-m)×(1-xy)]: [(1-m)×x+m×(2-z)]: 1: [m×z+(1-m)×y], wherein 0.01<x<0.9, 0.01<y≤0.1, 0.01<z≤0.1, 0.5≤m≤5%.

7. The method for preparing the lithium iron manganese phosphate composite material according to claim 6, characterized in that: In step S2, the pH value of the mixed solution A is adjusted to 0-6.0 using an acid solution; and / or, In step S4, the mixing method is dry grinding, and the grinding time is 30 to 60 minutes.

8. The method for preparing the lithium iron manganese phosphate composite material according to any one of claims 5 to 7, characterized in that: In step S4, the lithium element comes from one, two or more of lithium carbonate, lithium hydroxide and lithium oxalate; and / or, In step S1, the iron element comes from one, two or more of iron oxide, iron hydroxide, iron sulfate and iron oxalate; and / or, In step S1, the manganese element comes from one, two or more of manganese carbonate, manganous sulfate and manganese oxide; and / or, In step S1, the phosphorus element is selected from one, two or more of phosphoric acid, lithium dihydrogen phosphate and lithium hydrogen phosphate; and / or, In step S1, the boron element comes from one or both of boric acid and boron oxide.

9. The method for preparing the lithium iron manganese phosphate composite material according to claim 8, characterized in that: In step S4, the primary calcination and the secondary calcination are both performed under a protective atmosphere.

10. A lithium ion battery, comprising a positive electrode and a negative electrode, characterized in that: The positive electrode comprises the lithium iron manganese phosphate composite material as claimed in any one of claims 1 to 3 or the lithium iron manganese phosphate composite material prepared by the preparation method as claimed in any one of claims 4 to 9.

Citation Information

Patent Citations

  • Method for preparing lithium ion battery cathode material by coating lithium iron borate with graphene

    CN106450238A

  • Dual-composite modified spinel lithium manganate positive plate, preparation method thereof and lithium ion battery

    CN113054157A

  • Modified lithium ferric manganese phosphate material, and preparation method and application thereof

    CN113224278A

  • Lithium manganate / lithium manganese iron phosphate composite positive plate and lithium ion battery

    CN113823765A

  • Positive electrode material and preparation method thereof, positive electrode, lithium secondary battery and electric device

    CN115548299A